Fourier Transform Infrared Spectroscopy Analysis as a Tool to Address Aβ Impact on Extracellular Vesicles - Margarida Vaz; Tânia Soares Martins; Kevin Leandro; Luís Pereira de Almeida; Odete A. B. da Cruz e Silva; Alexandra Nunes; Ana Gabriela Henriques (Molecules)
Alzheimer’s disease is a challenge in modern healthcare due to its complex etiology and increasing prevalence. Despite advances, further understanding of Alzheimer’s disease pathophysiology is needed, particularly the role of Aβ neurotoxic peptide. Fourier transform infrared spectroscopy (FTIR) has shown potential as a screening tool for several pathologies, including Alzheimer’s disease. Nonetheless, limited research has explored Aβ direct effects on neurons and extracellular vesicles metabolic profiles. Hence, this study aims to investigate Aβ impact on the spectroscopic profiles of neuronal-like cells (N2a) and N2a-derived extracellular vesicles, employing FTIR spectroscopy and focusing on the 1280–900 cm−1 region. A comprehensive analysis of spectral data was carried out, including multivariate partial least squares (PLS) analysis and peak intensities analysis. PLS analysis revealed moderate to strong correlations within this spectral region for both N2a and N2a-derived extracellular vesicles. The peak intensity analysis revealed additional peaks with significant differences in EVs’ spectra relative to N2a, following Aβ treatment. Specifically, Aβ seems to cause alterations in protein phosphorylation and in the nucleic acids content of extracellular vesicles. These findings support that Aβ’s role in Alzheimer’s disease pathology may be mediated by extracellular vesicles and highlight FTIR’s potential for advancing Alzheimer’s disease research and clinical applications.